2017
DOI: 10.4236/msce.2017.59001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Carrier Conduction Mechanism over InAs/InP Quantum Dashes and InAs/GaAs Quantum Dots Based p-i-n Laser Heterostructures

Abstract: Charge transfer characteristics of the long wavelength semiconductor laser structures, containing quantum dot layers (QDs), were investigated by means of temperature dependent current-voltage and electroluminescence measurements over InAs/InP, and InAs/GaAs based p-i-n structures. In InAs/InP elongated QDs (QDashes) structure, injected carriers were tunneled from the quantum well into QDashes through a thin barrier and subsequently recombined within QDashes. Meanwhile, for InAs/GaAs structure, tunneling kind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The structure showed strong photoluminescence emissions were more efficient integration of NFGQDs exist as a result of the large ZnO surface area. Neslihan Ayarcı Kuruoğlu et al [6] investigate the Carrier Conduction Mechanism over InAs/InP Quantum Dashes and InAs/GaAs Quantum Dots Based p-i-n Laser Heterostructures. The charge transfer characteristics of the long wavelength semiconductor laser structures, containing quantum dot layers (QDs), were investigated by means of temperature dependent current-voltage and electroluminescence measurements over InAs/InP, and InAs/GaAs based p-i-n structures, they found that the peak value of emitted laser light for InAs/InP QDashes and InAs/GaAs QDs occurred in 1.55 μm and 1.3 μm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The structure showed strong photoluminescence emissions were more efficient integration of NFGQDs exist as a result of the large ZnO surface area. Neslihan Ayarcı Kuruoğlu et al [6] investigate the Carrier Conduction Mechanism over InAs/InP Quantum Dashes and InAs/GaAs Quantum Dots Based p-i-n Laser Heterostructures. The charge transfer characteristics of the long wavelength semiconductor laser structures, containing quantum dot layers (QDs), were investigated by means of temperature dependent current-voltage and electroluminescence measurements over InAs/InP, and InAs/GaAs based p-i-n structures, they found that the peak value of emitted laser light for InAs/InP QDashes and InAs/GaAs QDs occurred in 1.55 μm and 1.3 μm, respectively.…”
Section: Introductionmentioning
confidence: 99%